Cativas, degredadas e aventureiras: mulheres na colonização latino-americana - Ribeiro, Bruna Otani (2014)
Due to the patriarchal structure established in the Latin American continent since the beginning of European colonization, the female was assigned the role of taking care of the home, husband and children, following the teachings of the Catholic Church. In this sense, this research aims to analyze comparatively three historical extraction narratives: Lucía Miranda (1860), by Eduarda Mansilla, reedited by María Rosa Lojo, Desmundo (1996), by Ana Miranda, and Inés del alma mía (2006), by Isabel Allende, in order to understand how the fictional text approaches or moves away from historical texts taken as official and what is the relevance of these novels, considering that they evidence the active participation of women from Europe in the period of colonization and conquest of the New World , even though they were considered, during this historic moment, inferior to men. In this way, fiction, carrying out its critical reading of the past, reveals the presence of captive, exiled and adventurous European women , whose participation in the conquest of America is largely omitted by hegemonic discourse of history, which seeks only to make evident the male participation in this process. Showing this active participation of women in history, through the hybrid genre of history and fiction, means to enable new perspectives on the Latin American past. This is a study of the basic type, characterized as bibliographic, which will be supported by Comparative Literature. Some of the authors to be used as theoretical support are Linda Hutcheon (1991), Lucía Guerra (2007), Fernández Álvarez (2002), Gilmei Francisco Fleck (2007, 2010), Borges Teixeira (2008), among others. It is sought to show, through this study, that the narratives of female authors, especially those produced in contemporary times, are very important in view of the quest for gender opportunities equality